2019
DOI: 10.1186/s10194-019-1052-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced resting-state brain functional network connectivity and poor regional homogeneity in patients with CADASIL

Abstract: BackgroundCerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) manifests principally as a suite of cognitive impairments, particularly in the executive domain. Executive functioning requires the dynamic coordination of neural activity over large-scale networks. It remains unclear whether changes in resting-state brain functional network connectivity and regional homogeneities (ReHos) underly the mechanisms of executive dysfunction evident in CADASIL patients.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…Among them, FPN plays a vital role in spatial attention and motion control, such as target-oriented hand and eye movement (69), which are exactly what the Tai Chi Chuan exercise requires. What's more, as shown in Table 3, enhancing the FC of the bilateral cuneus in VN by Tai Chi Chuan was more effective in CFS patients, related to visual information processing and visuomotor planning (70). Consequently, we speculate that the change in the causal relationship between RFPN and VN is the neural basis for Tai Chi Chuan to improve the cognitive function of CFS patients, especially visual-spatial attention.…”
Section: Discussionmentioning
confidence: 75%
“…Among them, FPN plays a vital role in spatial attention and motion control, such as target-oriented hand and eye movement (69), which are exactly what the Tai Chi Chuan exercise requires. What's more, as shown in Table 3, enhancing the FC of the bilateral cuneus in VN by Tai Chi Chuan was more effective in CFS patients, related to visual information processing and visuomotor planning (70). Consequently, we speculate that the change in the causal relationship between RFPN and VN is the neural basis for Tai Chi Chuan to improve the cognitive function of CFS patients, especially visual-spatial attention.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have demonstrated the brain alterations in functional and structural imaging parameters in CADASIL patients. Our resting-state functional MRI (fMRI) studies showed that altered functional activity and connectivity in PCC/PCU and para-hippocampal cortex (PHC) were associated with cognitive impairment in CADASIL [11,12]. Diffusion tensor imaging (DTI) studies have demonstrated widespread white matter lesions associated with cognitive de cits in CADASIL [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
“…For example, in Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy, impaired cognitive function has been related to decreased intranetwork connectivity and reduced local brain activity. 53 Hypothesis-testing candidate gene approaches-querying associations between variants in specific genes and clinical traits-have also been used to explore possible genetic associations. Genes that have received interest include BDNF (brain-derived growth factor) and its rs6265 Val66Met variant (Table I in the Data Supplement), APOE (Apolipoprotein E), VEGF (vascular endothelial growth factor), COX-1 (cyclooxygenase-1), and COX-2 (cyclooxygenase-2).…”
Section: Using Genetics To Explore Mechanisms Underlying Stroke Outcomementioning
confidence: 99%